The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.2139/ssrn.272130
|View full text |Cite
|
Sign up to set email alerts
|

Kyoto Commitment and Emission Trading: A European Union Perspective

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Chevallier et al (2008) [6] found that the industrial production impact positively (negatively) the carbon market during periods of economic expansion (recession), confirming the relationship between macroeconomics and the price of carbon. (Burniaux (2000) [7], Ciorba et al (2001) [8], Sjim (2005) [9] and van der Mensbrugghe (1998)) in the same way showed that energy prices influence CO 2 prices. Redmond and Convery (2007) [10], Battaler et al (2013) [11], Alberola et al (2008) [6] and all studies including energy variables, assumed geometrical brownian motion process for modeling energy prices.…”
Section: Introductionmentioning
confidence: 98%
“…Chevallier et al (2008) [6] found that the industrial production impact positively (negatively) the carbon market during periods of economic expansion (recession), confirming the relationship between macroeconomics and the price of carbon. (Burniaux (2000) [7], Ciorba et al (2001) [8], Sjim (2005) [9] and van der Mensbrugghe (1998)) in the same way showed that energy prices influence CO 2 prices. Redmond and Convery (2007) [10], Battaler et al (2013) [11], Alberola et al (2008) [6] and all studies including energy variables, assumed geometrical brownian motion process for modeling energy prices.…”
Section: Introductionmentioning
confidence: 98%